Science Teacher Competence and Implementation of Authentic Learning Approach in Online Learning Modality and Student Academic Performance in Science - Amielyn B. Discipulo (RIRAI Publisher, 2024)
The science curriculum is designed to be learner-centered, constructivist, and inquiry-based, using evidence to build explanations. This study aimed to investigate the competence level of teachers in the implementation of an authentic learning approach. It employed a quantitative descriptive correlational design using an online survey among grade 10 junior high school science teachers and students from seven (7) private schools in Butuan City during the academic year 2021-2022. Results consistently indicated high teaching competence among science teachers in most schools; however, certain indicators such as gamification, Phet simulations, and conducting small-scale research still need to be implemented in some schools. Significant differences in competence and implementation of authentic learning approach were noted based on schools, attributed factors such as the use of learning management system, resource availability, and online training for teachers. Moreover, a significant relationship was found between the competence of teachers and the implementation of an authentic learning approach. The study also found a commendable level of proficiency in the academic performance of students. However, no significant relationship was observed between teacher competence and the implementation of an authentic learning approach to students' academic performance. These findings suggested that students cultivated a sense of independence in their learning process. It emphasized that empowering students to take ownership of their learning journey and leveraging teachers' expertise as facilitators lays the foundation for enhanced academic success in science education.